A method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as an aid.

CN121494595BActive Publication Date: 2026-10-16HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511901436.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-10-16
Estimated Expiration
2045-12-16

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了解决Ti3SiC2陶瓷与钛或钛铝合金钎焊连接时接头中易形成Ti5Si3脆性化合物,引起接头脆化,从而导致钎焊接头强度低的问题,而提供采用三维网络TiC纳米片辅助钎焊Ti3SiC2陶瓷与钛或钛铝合金的方法

Benefits of technology

本发明提出一种在钎焊接头中引入3D-TiCns的方法,利用其高孔隙率实现对钎缝中脆性化合物带的弥散强化,并且钎焊过程中Ti5Si3晶粒在3D-TiCns表面缺陷处的嵌入,在二者之间的界面处形成了Ti5Si3与TiC双相互锁的界面结构,通过机械互锁使界面强度进一步提高。此外,Ti5Si3相的弹性模量在TiC相与Ag-Cu基体之间,形成了3D-TiCns-TiC +Ti5Si3互锁界面区-Ti5Si3纳米层-AgCu基体的弹性模量多级过渡,增加了钎缝中增强相与基体间界面可靠性,从而显著增强3D-TiCns对钎缝组织的载荷传递强化效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121494595B_ABST
    Figure CN121494595B_ABST
Patent Text Reader

Abstract

This invention relates to the field of brazing ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets-assisted brazing. The purpose of this invention is to solve the problem of easy formation of brittle Ti5Si3 compounds in the joint during the brazing of Ti3SiC2 ceramics to titanium or titanium-aluminum alloys, leading to joint embrittlement and low brazed joint strength. Method: A method using Ti3SiC2 ceramics, 3D-TiC nanosheets, and other materials is described. ns The specimen to be brazed, consisting of Ag-Cu composite brazing filler metal and titanium or titanium-aluminum alloy, is placed in a vacuum furnace and heated to 840-900℃ under pressurized vacuum conditions, and held at 840-900℃ for 10-40 min; after holding, it is cooled. This invention provides a method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloy using three-dimensional network TiC nanosheets as an aid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of brazing ceramics with titanium or titanium-aluminum alloys, and specifically to a method for brazing Ti3SiC2 ceramics with titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets assisted by brazing. Background Technology

[0002] Currently, the manufacturing of key components for aero-engines involves various high-temperature resistant materials, primarily nickel-based superalloys. While nickel-based superalloys offer significant advantages in high-temperature strength, oxidation resistance, and hot corrosion resistance, their density is as high as 9.0 g / cm³. 3 This will greatly increase the load on the engine.

[0003] To improve the thrust-to-weight ratio of engines, new materials are needed to balance lightweight design and engine stability. The MAX phase is a ternary layered carbide / nitride, whose chemical formula can be represented as M... n+1 AX n In this MAX phase, M represents a transition metal, A represents a main group metal, and X represents a C / N element. These materials possess both the low density, high temperature resistance, high strength, and excellent oxidation resistance characteristic of ceramics, and the electrical conductivity, thermal conductivity, ease of processing, and impact resistance of metals. Leveraging these combined advantages of both ceramics and metals, MAX phase materials have demonstrated significant value in key applications such as high-temperature load-bearing components, power transmission parts, high-temperature heating elements, and nuclear fuel cladding, attracting widespread attention in the scientific research field. Ti3SiC2 is a MAX phase material that combines lightweight and stability. On one hand, the density of Ti3SiC2 ceramics is 4.46~4.53 g / cm³. 3 Ti3SiC2 ceramics are comparable to lightweight titanium and titanium-aluminum alloys. Furthermore, Ti3SiC2 ceramics exhibit stable chemical properties at high temperatures and good resistance to ablation. Therefore, reliably joining Ti3SiC2 ceramics with titanium and titanium-aluminum alloys to obtain ceramic-metal composite components possessing the excellent properties of both has significant theoretical and practical application value.

[0004] There are several challenges in joining Ti3SiC2 ceramics with titanium and titanium-aluminum alloys using brazing: the diffusion activation energy of Si in Ti3SiC2 is low, while Ti in titanium and titanium-aluminum alloys dissolves and diffuses into the brazing seam. Ti and Si have a strong affinity and easily react to form brittle Ti5Si3 compounds in the brazing seam, causing joint embrittlement and thus restricting the mechanical properties of the joint. Summary of the Invention

[0005] The purpose of this invention is to solve the problem that when Ti3SiC2 ceramics are brazed to titanium or titanium-aluminum alloys, brittle Ti5Si3 compounds are easily formed in the joint, causing joint embrittlement and resulting in low brazed joint strength. The invention provides a method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets.

[0006] The method of brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets is carried out according to the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; Ag-Cu-Ti powder was thoroughly mixed with a binder, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was placed in a vacuum furnace and heated to 840–900 °C under pressurized vacuum conditions, and held at 840–900 °C for 5–60 min. After the holding period, the sample was cooled to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated titanium or titanium-aluminum alloy are stacked together, with the Ti3SiC2 ceramic to be welded facing down and the titanium or titanium-aluminum alloy to be welded facing up, to obtain the test piece to be welded. The titanium or titanium-aluminum alloy mentioned is a Ti2AlNb alloy; Step S3: Vacuum brazing connection; The specimen to be welded obtained in step S2 is placed in a vacuum furnace and heated to 840~900℃ under pressurized vacuum conditions, and held at 840~900℃ for 10~40 min; after the holding period, it is cooled to complete the brazing of Ti3SiC2 ceramics with titanium or titanium-aluminum alloy assisted by three-dimensional network TiC nanosheets.

[0007] The principle of this invention: To address the interfacial embrittlement problem in brazing Ti3SiC2 ceramics with titanium and titanium-aluminum alloys, this invention proposes a brazing seam space segmentation control method, introducing three-dimensional network TiC nanosheets (3D-TiC). nsThis invention achieves the dispersion and refinement of brittle compound bands in the brazing seam. Since Ag-Cu brazing filler metal has poor wettability on Ti3SiC2, compared to traditional processes that completely block Ti diffusion by adding a barrier layer in the brazing seam, this invention dissolves Ti, which is more conducive to the wetting of Ti3SiC2 ceramics by the brazing filler metal. The specific principle is as follows: Cu atoms diffuse to the ceramic surface, replacing Si atoms in the Ti3SiC2 lattice. Free Si atoms enter the brazing filler metal, while Ti dissolves from the Ti2AlNb alloy matrix into the liquid brazing filler metal. Driven by the concentration gradient, Ti atoms diffuse towards the Ti3SiC2 ceramic side, reacting with the free Si released from the ceramic and Cu in the brazing filler metal to form brittle compound bands (Ti5Si3+TiCuSi), distributed in the brazing seam.

[0008] Furthermore, the three-dimensional network reinforcement phase in this invention can achieve bulk stress dispersion and transfer (the three-dimensional network structure, as a reinforcement phase, is uniformly distributed in the brazing matrix, and can transfer external loads in multiple directions through its continuous network structure, achieving uniform stress distribution in space, avoiding local stress concentration, and thus improving the overall load-bearing capacity of the joint), structural interlocking reinforcement, and crack propagation path deflection (the presence of the three-dimensional network structure causes frequent deflection and branching of cracks during propagation, preventing rapid propagation along a single plane, thereby lengthening the crack path, increasing the fracture surface energy, effectively inhibiting unstable crack propagation, and thus significantly improving the fracture toughness of the joint), thereby greatly improving the strength and toughness of the composite material. Compared with microscopic continuous reinforcement phases such as particle reinforcement, 3D-TiC ns It has a superior toughening effect.

[0009] The beneficial effects of this invention are: This invention proposes a method for introducing 3D-TiC into brazed joints. ns This method utilizes its high porosity to achieve dispersion strengthening of brittle compound bands in the brazing seam, and during brazing, Ti5Si3 grains are dispersed within 3D-TiC... ns The embedding of surface defects forms a double-interlocked interface structure of Ti5Si3 and TiC at the interface between the two phases, further enhancing the interface strength through mechanical interlocking. Furthermore, the elastic modulus of the Ti5Si3 phase is higher between the TiC phase and the Ag-Cu matrix, forming a 3D-TiC structure. ns The multi-level transition of the elastic modulus between the TiC + Ti5Si3 interlocking interface region, the Ti5Si3 nanolayer, and the AgCu matrix increases the interfacial reliability between the reinforcing phase and the matrix in the brazing seam, thereby significantly enhancing the 3D-TiC interlocking capability. ns The load transfer strengthening effect on the brazing seam structure.

[0010] This invention introduces 3D-TiC nsA three-dimensional network regulation of the distribution of brittle Ti5Si3 compounds was achieved, solving the problem of brittle compound agglomeration and enabling the nano-sizing of Ti5Si3 brittle compounds, thus alleviating stress concentration in the brittle phase. Simultaneously, 3D-TiC... ns Surface defects provide nucleation sites for Ti5Si3, allowing it to adhere to 3D-TiC. ns Grown as a nanolayer, Ti5Si3 nanolayer and 3D-TiC ns A double interlocking interface is formed between them (during the growth process, the Ti5Si3 phase fills and embeds itself into defects, pores, or grain boundaries on the surface of TiC nanosheets, forming an interlocking morphology similar to "mortise and tenon" or "puzzle"), which helps to improve the 3D-TiC... ns The load transfer strengthening effect changes the fracture mode from brittle fracture to ductile fracture, thereby significantly improving the connection strength of the brazed joint.

[0011] This invention provides a method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as an aid. Attached Figure Description

[0012] Figure 1 This indicates that 3D-TiC with a thickness of 200 µm was used in Example 1. ns Typical interface microstructure of a Ti3SiC2 ceramic-Ti2AlNb alloy brazed joint prepared by / Ag-Cu composite brazing filler metal under welding conditions of 840℃ connection temperature and 10 min holding time. Figure 2 This indicates that 3D-TiC with a thickness of 300 µm was used in Example 2. ns Typical interface microstructure of a Ti3SiC2 ceramic-Ti2AlNb alloy brazed joint prepared by / Ag-Cu composite brazing filler metal under welding conditions of 840℃ connection temperature and 20 min holding time; Figure 3 This indicates that 3D-TiC with a thickness of 200 µm was used in Example 3. ns Typical interface microstructure of a Ti3SiC2 ceramic-Ti2AlNb alloy brazed joint prepared by / Ag-Cu composite brazing filler metal under welding conditions of 880℃ connection temperature and 10 min holding time. Figure 4 This indicates that 3D-TiC with a thickness of 450 µm was used in Example 4. ns Typical interface microstructure of a Ti3SiC2 ceramic-Ti2AlNb alloy brazed joint prepared by / Ag-Cu composite brazing filler metal under welding conditions of 840℃ connection temperature and 10 min holding time. Figure 5 This indicates that 3D-TiC with a thickness of 600 µm was used in Example 5.ns Typical interface microstructure of a Ti3SiC2 ceramic-Ti2AlNb alloy brazed joint prepared by / Ag-Cu composite brazing filler metal under welding conditions of 840℃ connection temperature and 10 min holding time. Figure 6 This indicates that 3D-TiC with a thickness of 200 µm was used in Example 6. ns Typical interface microstructure of a Ti3SiC2 ceramic-Ti2AlNb alloy brazed joint prepared by / Ag-Cu composite brazing filler metal under welding conditions of 840℃ connection temperature and 30 min holding time; Figure 7 This diagram shows the distribution of Si elements at the Ti5Si3 / TiC interface in Example 1. Detailed Implementation

[0013] Specific Implementation Method 1: This implementation method uses a three-dimensional network TiC nanosheet-assisted brazing method to bond Ti3SiC2 ceramics to titanium or titanium-aluminum alloys, and is carried out according to the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; Ag-Cu-Ti powder was thoroughly mixed with a binder, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was placed in a vacuum furnace and heated to 840–900 °C under pressurized vacuum conditions, and held at 840–900 °C for 5–60 min. After the holding period, the sample was cooled to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated titanium or titanium-aluminum alloy are stacked together, with the Ti3SiC2 ceramic to be welded facing down and the titanium or titanium-aluminum alloy to be welded facing up, to obtain the test piece to be welded. The titanium or titanium-aluminum alloy mentioned is a Ti2AlNb alloy; Step S3: Vacuum brazing connection; The specimen to be welded obtained in step S2 is placed in a vacuum furnace and heated to 840~900℃ under pressurized vacuum conditions, and held at 840~900℃ for 10~40 min; after the holding period, it is cooled to complete the brazing of Ti3SiC2 ceramics with titanium or titanium-aluminum alloy assisted by three-dimensional network TiC nanosheets.

[0014] Specific Implementation Method Two: The difference between this implementation method and Specific Implementation Method One is that the Ag-Cu-Ti powder mentioned in step S1 is composed of AgCu28 eutectic powder and Ti powder, and the Ti powder accounts for 4.5% of the mass fraction of the Ag-Cu-Ti powder.

[0015] The other steps are the same as in Specific Implementation Method 1.

[0016] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that: in step S1, when the sample is placed into the vacuum furnace, graphite paper is used to isolate the sample from the tray in the vacuum furnace; the vacuum degree in step S1 is 7×10⁻⁶. -4 Pa~5×10 -3 Pa.

[0017] The other steps are the same as in Specific Implementation Method 1 or 2.

[0018] Specific Implementation Method Four: The difference between this implementation method and Specific Implementation Methods One to Three is that in step S1, the temperature is increased to 840-900℃ at a heating rate of 5-10℃ / min; after the heat preservation is completed, the temperature is cooled to ≤200℃.

[0019] The other steps are the same as those in Specific Implementation Methods One to Three.

[0020] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the pretreated Ti3SiC2 ceramic described in step S2 is pretreated according to the following steps: Cut the Ti3SiC2 ceramic, and polish the surface to be welded with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit and 1500 grit sandpaper in sequence. Then put it into alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 20~100 kHz for 5~10 minutes. Change the alcohol or acetone and repeat the cleaning 2~3 times.

[0021] The other steps are the same as those in Specific Implementation Methods One through Four.

[0022] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the pretreated titanium or titanium-aluminum alloy described in step S2 is pretreated according to the following steps: Cut the titanium and titanium-aluminum alloy, and polish the surfaces to be welded with sandpaper of 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit and 1500 grit in sequence. Then put them into alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean them at a frequency of 20~100 kHz for 5~10 minutes. Change the alcohol or acetone and repeat the cleaning 2~3 times.

[0023] The other steps are the same as those in Specific Implementation Methods 1 to 5.

[0024] Specific Implementation Method Seven: The difference between this implementation method and Specific Implementation Methods One to Six is ​​that the pre-processed 3D-TiC described in step S2... ns / Ag-Cu composite solder is pretreated according to the following steps: 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 150~600 µm and a size of (5~7) mm × (5~7) mm. It is then polished with 1000~2000 grit sandpaper, and then placed in alcohol or acetone. It is then ultrasonically cleaned for 5~10 min at a frequency of 20~100 kHz using an ultrasonic cleaner. The alcohol or acetone is changed and the cleaning is repeated 2~3 times.

[0025] The other steps are the same as those in Specific Implementation Methods 1 to 6.

[0026] Specific Implementation Method Eight: The difference between this implementation method and Specific Implementation Methods One through Seven is that the vacuum degree in step S3 is 7 × 10⁻⁶. -4 Pa~5×10 -3 Pa.

[0027] The other steps are the same as those in Specific Implementation Methods 1 to 7.

[0028] Specific Implementation Method Nine: The difference between this implementation method and Specific Implementation Methods One to Eight is that in step S3, the temperature is increased to 840-900℃ at a heating rate of 5-10℃ / min.

[0029] The other steps are the same as those in Specific Implementation Methods 1 to 8.

[0030] Specific Implementation Method 10: The difference between this implementation method and Specific Implementation Methods 1 to 9 is that after the heat preservation is completed in step S3, the temperature is cooled to ≤200℃.

[0031] The other steps are the same as those in Specific Implementation Methods 1 to 9.

[0032] The beneficial effects of the present invention are verified using the following embodiments: Example 1: A method for brazing Ti3SiC2 ceramic and Ti2AlNb alloy using three-dimensional network TiC nanosheets as an aid, comprising the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; First, a 5 mm thick three-dimensional network graphene sheet was cut using a thin blade to ensure high parallelism between its upper and lower surfaces. Ag-Cu-Ti powder was thoroughly mixed with a binder to form a paste, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was loaded into a vacuum furnace. Graphite paper was used to isolate the sample from the tray in the vacuum furnace to prevent the Ag-Cu-Ti solder from reacting with the tray, forming adhesion, and consuming the Ti element in the solder. After loading into the furnace, the sample was subjected to a 5 × 10⁻⁶ molten metal furnace. -3 Under a vacuum of Pa, the temperature was increased to 880℃ at a heating rate of 10℃ / min and held at 880℃ for 30 min. After holding, the temperature was cooled to 20~200℃ and removed from the furnace to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Pre-welding treatment of Ti3SiC2 ceramic; Cut Ti3SiC2 ceramic into 5 mm × 5 mm × 5 mm pieces. Grind the surfaces to be soldered sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, place the ceramic in alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 100 kHz for 10 minutes. Repeat the cleaning process three times with different amounts of alcohol or acetone. After cleaning, place the ceramic in acetone for liquid sealing and use later. Step S3: Pre-welding treatment of Ti2AlNb alloy; The Ti2AlNb alloy was cut into 10 mm × 10 mm × 3 mm pieces. The surfaces to be welded were polished sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, the surfaces were placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 minutes. The alcohol or acetone was changed and the cleaning was repeated 3 times. After cleaning, the surfaces were sealed in acetone for later use. Step S4: 3D-TiC ns Pre-welding treatment of Ag-Cu composite solder; 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 200 µm and a size of 6 mm × 6 mm (slightly larger than the size of Ti3SiC2 ceramic). It is then polished with 1500 grit sandpaper to ensure a smooth surface. It is then placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 min. The alcohol or acetone is changed and the cleaning is repeated 3 times. After cleaning, it is placed in acetone for liquid sealing and later use. Step S5: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated Ti2AlNb alloy are stacked with the Ti3SiC2 ceramic facing down and the Ti2AlNb alloy facing up to obtain the test piece to be welded; Step S6: Vacuum brazing connection; The test piece to be welded was placed in a vacuum furnace and heated at 5×10⁻⁶. -3 Under a vacuum of Pa, the sample was heated to 840℃ at a heating rate of 10℃ / min and held at 840℃ for 10 min. After holding, the sample was cooled to 20~200℃ and then removed to obtain a brazed joint (e.g., Figure 1 (As shown).

[0033] Shear tests were performed using an electronic universal testing machine at a loading speed of 0.5 mm / min. This embodiment utilizes 3D-TiC... ns The brazing of Ti3SiC2 ceramic and Ti2AlNb alloy with Ag-Cu composite brazing filler metal resulted in a room temperature shear strength of 203 MPa, which is 78% of the shear strength of the Ti3SiC2 ceramic base material (the shear strength of the Ti3SiC2 ceramic base material is 260 MPa). In contrast, the room temperature shear strength of brazing with AgCu filler metal in conventional processes is only 89 MPa.

[0034] Example 2: A method for brazing Ti3SiC2 ceramic and Ti2AlNb alloy using three-dimensional network TiC nanosheets as an aid, comprising the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; First, an 8 mm thick three-dimensional network graphene sheet was cut using a thin blade to ensure high parallelism between its upper and lower surfaces. Ag-Cu-Ti powder was thoroughly mixed with a binder to form a paste, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was loaded into a vacuum furnace. Graphite paper was used to isolate the sample from the tray in the vacuum furnace to prevent the Ag-Cu-Ti solder from reacting with the tray, forming adhesion, and consuming the Ti element in the solder. After loading into the furnace, the sample was subjected to a 5 × 10⁻⁶ molten metal furnace. -3 Under a vacuum of Pa, the temperature was increased to 860℃ at a heating rate of 10℃ / min and held at 860℃ for 30 min. After holding, the temperature was cooled to 20~200℃ and removed from the furnace to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Pre-welding treatment of Ti3SiC2 ceramic; Cut Ti3SiC2 ceramic into 5 mm × 5 mm × 5 mm pieces. Grind the surfaces to be soldered sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, place the ceramic in alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 100 kHz for 10 minutes. Repeat the cleaning process three times with different amounts of alcohol or acetone. After cleaning, place the ceramic in acetone for liquid sealing and use later. Step S3: Pre-welding treatment of Ti2AlNb alloy; The Ti2AlNb alloy was cut into 10 mm × 10 mm × 3 mm pieces. The surfaces to be welded were polished sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, the surfaces were placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 minutes. The alcohol or acetone was changed and the cleaning was repeated 3 times. After cleaning, the surfaces were sealed in acetone for later use. Step S4: 3D-TiC ns Pre-welding treatment of Ag-Cu composite solder; 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 300 µm and a size of 6 mm × 6 mm. It is then polished with 1500 grit sandpaper to ensure a smooth surface. It is then placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 min. The alcohol or acetone is changed and the cleaning is repeated 3 times. After cleaning, it is placed in acetone for liquid sealing and later use. Step S5: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated Ti2AlNb alloy are stacked with the Ti3SiC2 ceramic facing down and the Ti2AlNb alloy facing up to obtain the test piece to be welded; Step S6: Vacuum brazing connection; The test piece to be welded was placed in a vacuum furnace and heated at 5×10⁻⁶. -3 Under a vacuum of Pa, the sample was heated to 840℃ at a heating rate of 10℃ / min and held at 840℃ for 20 min. After holding, the sample was cooled to 20~200℃ and then removed to obtain a brazed joint (e.g., Figure 2 (As shown).

[0035] Shear tests were performed using an electronic universal testing machine at a loading speed of 0.5 mm / min. This embodiment utilizes 3D-TiC... nsThe brazing of Ti3SiC2 ceramic and Ti2AlNb alloy with Ag-Cu composite brazing filler metal resulted in a joint with a room temperature shear strength of 185 MPa.

[0036] Example 3: A method for brazing Ti3SiC2 ceramic and Ti2AlNb alloy using three-dimensional network TiC nanosheets as an aid, comprising the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; First, a 10 mm thick three-dimensional network graphene sheet was cut using a thin blade to ensure high parallelism between its upper and lower surfaces. Ag-Cu-Ti powder was thoroughly mixed with a binder to form a paste, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was loaded into a vacuum furnace. Graphite paper was used to isolate the sample from the tray in the vacuum furnace to prevent the Ag-Cu-Ti solder from reacting with the tray, forming adhesion, and consuming the Ti element in the solder. After loading into the furnace, the sample was subjected to a 5 × 10⁻⁶ molten metal furnace. -3 Under a vacuum of Pa, the temperature was increased to 860℃ at a heating rate of 10℃ / min and held at 860℃ for 60 min. After holding, the temperature was cooled to 20~200℃ and removed from the furnace to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Pre-welding treatment of Ti3SiC2 ceramic; Cut Ti3SiC2 ceramic into 5 mm × 5 mm × 5 mm pieces. Grind the surfaces to be soldered sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, place the ceramic in alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 100 kHz for 10 minutes. Repeat the cleaning process three times with different amounts of alcohol or acetone. After cleaning, place the ceramic in acetone for liquid sealing and use later. Step S3: Pre-welding treatment of Ti2AlNb alloy; The Ti2AlNb alloy was cut into 10 mm × 10 mm × 3 mm pieces. The surfaces to be welded were polished sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, the surfaces were placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 minutes. The alcohol or acetone was changed and the cleaning was repeated 3 times. After cleaning, the surfaces were sealed in acetone for later use. Step S4: 3D-TiC ns Pre-welding treatment of Ag-Cu composite solder; 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 200 µm and a size of 6 mm × 6 mm. It is then polished with 1500 grit sandpaper to ensure a smooth surface. It is then placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 min. The alcohol or acetone is changed and the cleaning is repeated 3 times. After cleaning, it is placed in acetone for liquid sealing and later use. Step S5: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated Ti2AlNb alloy are stacked with the Ti3SiC2 ceramic facing down and the Ti2AlNb alloy facing up to obtain the test piece to be welded; Step S6: Vacuum brazing connection; The test piece to be welded was placed in a vacuum furnace and heated at 5×10⁻⁶. -3 Under a vacuum of Pa, the sample was heated to 880℃ at a heating rate of 10℃ / min and held at 880℃ for 10 min. After holding, the sample was cooled to 20~200℃ and then removed to obtain a brazed joint (e.g., Figure 3 (As shown).

[0037] Shear tests were performed using an electronic universal testing machine at a loading speed of 0.5 mm / min. This embodiment utilizes 3D-TiC... ns The brazing of Ti3SiC2 ceramic and Ti2AlNb alloy with Ag-Cu composite brazing filler metal resulted in a joint with a room temperature shear strength of 173 MPa.

[0038] Example 4: A method for brazing Ti3SiC2 ceramic and Ti2AlNb alloy using three-dimensional network TiC nanosheets as an aid, comprising the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; First, a 10 mm thick three-dimensional network graphene sheet was cut using a thin blade to ensure high parallelism between its upper and lower surfaces. Ag-Cu-Ti powder was thoroughly mixed with a binder to form a paste, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was loaded into a vacuum furnace. Graphite paper was used to isolate the sample from the tray in the vacuum furnace to prevent the Ag-Cu-Ti solder from reacting with the tray, forming adhesion, and consuming the Ti element in the solder. After loading into the furnace, the sample was subjected to a 5 × 10⁻⁶ molten metal furnace. -3 Under a vacuum of Pa, the temperature was increased to 860℃ at a heating rate of 10℃ / min and held at 860℃ for 60 min. After holding, the temperature was cooled to 20~200℃ and removed from the furnace to obtain 3D-TiC.ns / Ag-Cu composite solder; Step S2: Pre-welding treatment of Ti3SiC2 ceramic; Cut Ti3SiC2 ceramic into 5 mm × 5 mm × 5 mm pieces. Grind the surfaces to be soldered sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, place the ceramic in alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 100 kHz for 10 minutes. Repeat the cleaning process three times with different amounts of alcohol or acetone. After cleaning, place the ceramic in acetone for liquid sealing and use later. Step S3: Pre-welding treatment of Ti2AlNb alloy; The Ti2AlNb alloy was cut into 10 mm × 10 mm × 3 mm pieces. The surfaces to be welded were polished sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, the surfaces were placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 minutes. The alcohol or acetone was changed and the cleaning was repeated 3 times. After cleaning, the surfaces were sealed in acetone for later use. Step S4: 3D-TiC ns Pre-welding treatment of Ag-Cu composite solder; 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 450 µm and a size of 6 mm × 6 mm. It is then polished with 1500 grit sandpaper to ensure a smooth surface. It is then placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 min. The alcohol or acetone is changed and the cleaning is repeated 3 times. After cleaning, it is placed in acetone for liquid sealing and later use. Step S5: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated Ti2AlNb alloy are stacked with the Ti3SiC2 ceramic facing down and the Ti2AlNb alloy facing up to obtain the test piece to be welded; Step S6: Vacuum brazing connection; The test piece to be welded was placed in a vacuum furnace and heated at 5×10⁻⁶. -3 Under a vacuum of Pa, the sample was heated to 840℃ at a heating rate of 10℃ / min and held at 840℃ for 10 min. After holding, the sample was cooled to 20~200℃ and then removed to obtain a brazed joint (e.g., Figure 4 (As shown).

[0039] Shear tests were performed using an electronic universal testing machine at a loading speed of 0.5 mm / min. This embodiment utilizes 3D-TiC... ns The brazing of Ti3SiC2 ceramic and Ti2AlNb alloy with Ag-Cu composite brazing filler metal resulted in a joint with a room temperature shear strength of 197 MPa.

[0040] Example 5: A method for brazing Ti3SiC2 ceramic and Ti2AlNb alloy using three-dimensional network TiC nanosheets as an aid, comprising the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; First, a 5 mm thick three-dimensional network graphene sheet was cut using a thin blade to ensure high parallelism between its upper and lower surfaces. Ag-Cu-Ti powder was thoroughly mixed with a binder to form a paste, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was loaded into a vacuum furnace. Graphite paper was used to isolate the sample from the tray in the vacuum furnace to prevent the Ag-Cu-Ti solder from reacting with the tray, forming adhesion, and consuming the Ti element in the solder. After loading into the furnace, the sample was subjected to a 5 × 10⁻⁶ molten metal furnace. -3 Under a vacuum of Pa, the temperature was increased to 860℃ at a heating rate of 10℃ / min and held at 860℃ for 30 min. After holding, the temperature was cooled to 20~200℃ and removed from the furnace to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Pre-welding treatment of Ti3SiC2 ceramic; Cut Ti3SiC2 ceramic into 5 mm × 5 mm × 5 mm pieces. Grind the surfaces to be soldered sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, place the ceramic in alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 100 kHz for 10 minutes. Repeat the cleaning process three times with different amounts of alcohol or acetone. After cleaning, place the ceramic in acetone for liquid sealing and use later. Step S3: Pre-welding treatment of Ti2AlNb alloy; The Ti2AlNb alloy was cut into 10 mm × 10 mm × 3 mm pieces. The surfaces to be welded were polished sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, the surfaces were placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 minutes. The alcohol or acetone was changed and the cleaning was repeated 3 times. After cleaning, the surfaces were sealed in acetone for later use. Step S4: 3D-TiC nsPre-welding treatment of Ag-Cu composite solder; 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 600 µm and a size of 6 mm × 6 mm. It is then polished with 1500 grit sandpaper to ensure a smooth surface. It is then placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 min. The alcohol or acetone is changed and the cleaning is repeated 3 times. After cleaning, it is placed in acetone for liquid sealing and later use. Step S5: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated Ti2AlNb alloy are stacked with the Ti3SiC2 ceramic facing down and the Ti2AlNb alloy facing up to obtain the test piece to be welded; Step S6: Vacuum brazing connection; The test piece to be welded was placed in a vacuum furnace and heated at 5×10⁻⁶. -3 Under a vacuum of Pa, the sample was heated to 840℃ at a heating rate of 10℃ / min and held at 840℃ for 10 min. After holding, the sample was cooled to 20~200℃ and then removed to obtain a brazed joint (e.g., Figure 5 (As shown).

[0041] Shear tests were performed using an electronic universal testing machine at a loading speed of 0.5 mm / min. This embodiment utilizes 3D-TiC... ns The brazing of Ti3SiC2 ceramic and Ti2AlNb alloy with Ag-Cu composite brazing filler metal resulted in a joint with a room temperature shear strength of 162 MPa.

[0042] Example 6: A method for brazing Ti3SiC2 ceramic and Ti2AlNb alloy using three-dimensional network TiC nanosheets as an aid, comprising the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; First, an 8 mm thick three-dimensional network graphene sheet was cut using a thin blade to ensure high parallelism between its upper and lower surfaces. Ag-Cu-Ti powder was thoroughly mixed with a binder to form a paste, dried, and then shaped to obtain Ag-Cu-Ti solder. The Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets, and the sample was loaded into a vacuum furnace. Graphite paper was used to isolate the sample from the tray in the vacuum furnace to prevent the Ag-Cu-Ti solder from reacting with the tray, forming adhesion, and consuming the Ti element in the solder. After loading into the furnace, the sample was subjected to a 5 × 10⁻⁶ molten metal furnace. -3Under a vacuum of Pa, the temperature was increased to 860℃ at a heating rate of 10℃ / min and held at 860℃ for 60 min. After holding, the temperature was cooled to 20~200℃ and removed from the furnace to obtain 3D-TiC. ns / Ag-Cu composite solder; Step S2: Pre-welding treatment of Ti3SiC2 ceramic; Cut Ti3SiC2 ceramic into 5 mm × 5 mm × 5 mm pieces. Grind the surfaces to be soldered sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, place the ceramic in alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 100 kHz for 10 minutes. Repeat the cleaning process three times with different amounts of alcohol or acetone. After cleaning, place the ceramic in acetone for liquid sealing and use later. Step S3: Pre-welding treatment of Ti2AlNb alloy; The Ti2AlNb alloy was cut into 10 mm × 10 mm × 3 mm pieces. The surfaces to be welded were polished sequentially with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit, and 1500 grit sandpaper to remove surface impurities and ensure a smooth and flat surface. Then, the surfaces were placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 minutes. The alcohol or acetone was changed and the cleaning was repeated 3 times. After cleaning, the surfaces were sealed in acetone for later use. Step S4: 3D-TiC ns Pre-welding treatment of Ag-Cu composite solder; 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 200 µm and a size of 6 mm × 6 mm. It is then polished with 1500 grit sandpaper to ensure a smooth surface. It is then placed in alcohol or acetone and ultrasonically cleaned at a frequency of 100 kHz for 10 min. The alcohol or acetone is changed and the cleaning is repeated 3 times. After cleaning, it is placed in acetone for liquid sealing and later use. Step S5: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated Ti2AlNb alloy are stacked with the Ti3SiC2 ceramic facing down and the Ti2AlNb alloy facing up to obtain the test piece to be welded; Step S6: Vacuum brazing connection; The test piece to be welded was placed in a vacuum furnace and heated at 5×10⁻⁶. -3Under a vacuum of Pa, the sample was heated to 840℃ at a heating rate of 10℃ / min and held at 840℃ for 30 min. After holding, the sample was cooled to 20~200℃ and then removed to obtain a brazed joint (e.g., Figure 6 (As shown).

[0043] Shear tests were performed using an electronic universal testing machine at a loading speed of 0.5 mm / min. This embodiment utilizes 3D-TiC... ns The brazing of Ti3SiC2 ceramic and Ti2AlNb alloy with Ag-Cu composite brazing filler metal resulted in a joint with a room temperature shear strength of 178 MPa.

[0044] The three-dimensional network graphene sheets used in Examples 1-6 were purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the Ag-Cu-Ti powder used was purchased from Zhongnuo New Materials (Beijing) Technology Co., Ltd. The Ag-Cu-Ti powder was composed of AgCu28 eutectic powder and Ti powder, with Ti powder accounting for 4.5% of the mass fraction of Ag-Cu-Ti powder; the vacuum furnace used was a domestic VAF-30 vacuum furnace.

[0045] from Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 It can be seen that at a brazing temperature of 840~880℃, a holding time of 10~30 min, and 3D-TiC ns Within the brazing experimental parameters of Ag-Cu composite solder thickness ranging from 200 to 600 µm, 3D-TiC was introduced. ns The nanostructuring of brittle compounds was achieved, alleviating stress concentration in the brittle phase, and the Ti5Si3 nanolayer combined with 3D-TiC ns A double interlocking interface is formed between them (see Figure 7 (The area indicated by the red arrow in the middle) significantly improved 3D-TiC ns The load transfer enhancement effect.

[0046] At the same time, the following conclusions can be drawn: 1. The thickness of the brazing filler metal affects the content of the three-dimensional network structure, the uniformity of the brittle phase distribution, and the interfacial thermal stress in the brazing seam. If the brazing filler metal is too thin, 3D-TiC... ns Low content leads to brittle phase agglomeration, severe stress concentration, and low strength; excessively thick brazing filler metal results in increased interfacial thermal stress due to differences in thermal expansion coefficients, which easily induces cracks and reduces strength. 2. Brazing temperature affects the interfacial reaction rate, base metal dissolution, and the formation and morphology of brittle phases. At low temperatures, the interfacial reaction is insufficient, resulting in weak bonding; the brittle phase is granular and easily becomes a crack initiation site; at excessively high temperatures, the brittle phase layer thickens excessively, making it prone to cracking.

[0047] 3. The heat preservation time controls the thickness of the reaction layer, the degree of element diffusion, and the size and distribution of the brittle phase. If the time is too short, the element diffusion is insufficient, the brittle phase is not homogenized, and it remains as agglomerated particles with low strength; if the time is too long, the brittle phase layer is too thick, the parent material is excessively dissolved, and the interfacial reaction layer thickens.

Claims

1. A method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as an auxiliary agent, characterized in that, This method is performed in the following steps: Step S1: 3D-TiC ns Preparation of Ag-Cu composite solder; Ag-Cu-Ti powder is thoroughly mixed with binder, dried, and then shaped to obtain Ag-Cu-Ti solder. Ag-Cu-Ti solder was placed between two three-dimensional network graphene sheets. The sample was then placed in a vacuum furnace and heated to 840–900 °C under pressurized vacuum conditions, and held at 840–900 °C for 5–60 min. After the holding period, the sample was cooled to obtain 3D-TiC. ns / Ag-Cu composite solder; The Ag-Cu-Ti powder mentioned in step S1 is composed of AgCu28 eutectic powder and Ti powder, wherein the Ti powder accounts for 4.5% of the mass fraction of the Ag-Cu-Ti powder. In step S1, when loading the sample into the vacuum furnace, graphite paper is used to isolate the sample from the tray in the vacuum furnace; the vacuum level in step S1 is 7 × 10⁻⁶. -4 Pa~5×10 -3 Pa; In step S1, heat to 840-900℃ at a heating rate of 5-10℃ / min; after holding at that temperature, cool to ≤200℃. Step S2: Assembly of the test piece to be welded; The pretreated Ti3SiC2 ceramic and the pretreated 3D-TiC ceramic are arranged in the following order from top to bottom: ns / Ag-Cu composite solder and pretreated titanium or titanium-aluminum alloy are stacked together, with the Ti3SiC2 ceramic to be welded facing down and the titanium or titanium-aluminum alloy to be welded facing up, to obtain the test piece to be welded. The titanium or titanium-aluminum alloy mentioned is a Ti2AlNb alloy; Step S3: Vacuum brazing connection; The specimen to be welded obtained in step S2 is placed in a vacuum furnace and heated to 840~900℃ under pressurized vacuum conditions, and held at 840~900℃ for 10~40 min; after the holding period, it is cooled to complete the brazing of Ti3SiC2 ceramics with titanium or titanium-aluminum alloy assisted by three-dimensional network TiC nanosheets.

2. The method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as described in claim 1, characterized in that, The pretreated Ti3SiC2 ceramic described in step S2 shall be pretreated according to the following steps: Cut the Ti3SiC2 ceramic, and polish the surface to be welded with 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit and 1500 grit sandpaper in sequence. Then put it into alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean it at a frequency of 20~100 kHz for 5~10 minutes. Change the alcohol or acetone and repeat the cleaning 2~3 times.

3. The method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as described in claim 1, characterized in that... The pretreated titanium or titanium-aluminum alloy described in step S2 shall be pretreated according to the following steps: Cut the titanium and titanium-aluminum alloy, and polish the surfaces to be welded with sandpaper of 400 grit, 600 grit, 800 grit, 1000 grit, 1200 grit and 1500 grit in sequence. Then put them into alcohol or acetone and use an ultrasonic cleaner to ultrasonically clean them at a frequency of 20~100 kHz for 5~10 minutes. Change the alcohol or acetone and repeat the cleaning 2~3 times.

4. The method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as described in claim 1, characterized in that... The pretreated 3D-TiC described in step S2 ns / Ag-Cu composite solder is pretreated according to the following steps: 3D-TiC ns / Ag-Cu composite brazing filler metal is cut to a thickness of 150~600 µm and a size of (5~7) mm × (5~7) mm. It is then polished with 1000~2000 grit sandpaper, and then placed in alcohol or acetone. It is then ultrasonically cleaned for 5~10 min at a frequency of 20~100 kHz using an ultrasonic cleaner. The alcohol or acetone is changed and the cleaning is repeated 2~3 times.

5. The method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as described in claim 1, characterized in that... The vacuum degree in step S3 is 7×10 -4 Pa~5×10 -3 Pa.

6. The method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as described in claim 1, characterized in that, In step S3, the temperature is increased to 840-900℃ at a heating rate of 5-10℃ / min.

7. The method for brazing Ti3SiC2 ceramics to titanium or titanium-aluminum alloys using three-dimensional network TiC nanosheets as described in claim 1, characterized in that, After the heat preservation in step S3 is completed, cool to ≤200℃.

Citation Information

Patent Citations

  • Brake disc polishing material and preparation method thereof

    CN106431409A

  • High temperature conductive composite material and method of manufacturing the same

    JP2002080280A